Provider understandings of and attitudes towards integration: Implementing an HIV and sexual and reproductive health service integration model, South Africa. Issue 2 (3rd April 2018) - Milford, Cecilia; Greener, Letitia Rambally; Beksinska, Mags; Greener, Ross; Mabude, Zonke; Smit, Jenni
Abstract : In South Africa, a lack of integration between sexual and reproductive health (SRH) and HIV services has led to lost opportunities in the treatment cascade. In a context of high HIV, tuberculosis (TB) and unplanned pregnancies, a model for integrating SRH and HIV services was implemented in a hospital and six feeder clinics in KwaZulu-Natal, South Africa. Changes in healthcare provider knowledge, attitudes and understandings were explored following model implementation. Baseline data were collected via focus group discussions (FGDs) and a cross-sectional survey, and were used to inform the development of a model for integrating SRH and HIV services. Following the implementation of the model, an endline survey was conducted to explore any changes. Four FGDs were conducted with healthcare providers at study facilities. A total of 46 providers participated in the baseline survey, and 44 in the endline survey. Qualitative data were thematically analysed using NVivo 11, and quantitative data were descriptively analysed using SPSS 24. The understanding of integration improved by endline. Integration of services was considered important for reducing stigma and increasing access to and improving quality of care. Concerns raised were that integration would increase workload and time per client. Physical structure of facilities was not always conducive to referral or integration. Perceived benefits of integration and actual integration of services improved between baseline and endline. Enhanced understanding of integration and increased levels of reported integration over time imply that providers are more aware, suggesting that the model was effective. Provider perspectives and understandings are important for the successful integration of services. This integration model is relevant and useful to inform training and mentoring of providers, as well as to provide recommendations for policy implementation.